Microcalorimetric study of the growth of Streptococcus thermophilus in renneted milk - Stulova, Irina; Kabanova, Natalja; Kriščiunaite, Tiina; Adamberg, Kaarel; Laht, Tiiu-Maie; Vilu, Raivo (Frontiers in Microbiology, 2015)
The growth of Streptococcus thermophilus ST12 (ST12) in liquid milk, reconstituted from low-heat skim milk powder (RSM) and in RSM with rennet addition (r-RSM) at 40°C was monitored by microcalorimetry. It was shown that the growth rate of bacteria decreased in renneted samples in comparison with liquid RSM starting from certain sizes of the colonies (“deviation moments”), which depended on the inoculation rates. The hydrolysis of lactose was delayed for about 1 h in the r-RSM in comparison with RSM but otherwise the metabolism of carbohydrates in the renneted and non-renneted milks was similar. The total free amino acids content by the end of fermentations was higher in r-RSM than in RSM presumably due to the enzymatic hydrolytic activity of rennet. The quantitatively dominating amino acids were remarkably different in the r-RSM and RSM indicating that the hydrolysis cascade of caseins and/or metabolism of amino acids by the bacteria functioned differently in the two cases. The data obtained showed potential of microcalorimetry to characterize quantitative differences of growth and metabolism of the bacteria in renneted and liquid samples of milk.